Results of rearing Siberian sturgeon in cages in the European North - Volkova Anna; Muraviya Larisa (BIO Web of Conferences)
The article presents the materials on the study of the influence of stocking density and temperature conditions on the results of growing Siberian sturgeon (Acipenser Baerii Brandt) in cages. The material for the study was a group of yearlings of Siberian sturgeon. The planting material was divided into experimental groups with different stocking densities -70, 132 and 194 pcs/m2 and placed in cages installed in reservoirs with different temperature conditions - with thermal constants of 1142 and 1580 degree-days. The aim of the work was to evaluate the joint effect of stocking density and water temperature on growth, dynamics of changes in linear-weight and morphometric parameters of sturgeon grown in cages for 97 days. For this purpose, we assessed the fish farming and biological, morphometric parameters and determined the influence of these factors on the morphometric characteristics of sturgeon fingerlings. As a result of the study, a reliable increase in fish weight was noted when kept in groups with a stocking density of 132 pcs/m2, under different temperature conditions. In the cage with a more optimal temperature of 1580 degree-days, the fish weight by the end of rearing was significantly greater and made 199 g, while the increase in stocking density did not have a negative effect on the rearing results and contributed to a more efficient use of production areas. We noted the highest average daily, relative weight gain and higher values of morphometric indicators in the same group. Single-factor analysis of variance showed that the effect of stocking density on linear-weight and morphometric parameters was low and unreliable.